Induction of diploid gynogenesis in the catfish, Clarias batrachus (Linnaeus, 1758) using cold shock technique - Karal Marx, K. (Indian Journal of Fisheries, 2011)
Gynogenetic diploidy was induced in the catfish, Clarias batrachus by applying cold shock to the eggs after fertilization with spermatozoa genetically inactivated by ultraviolet-ray irradiation. The heterologous sperm was inactivated through UV-irradiation (254 nm) at a constant distance of 20 cm from top and bottom lamp-sperm. Irradiation for a duration of 60-120 seconds showed more than 70% motility for a duration of 3.5-4.0 min. Gynogenetic diploidy was induced by restoring second polar body by cold shock at 1 °C and 2 °C for a duration of 15, 30, and 45 min, initiated 4 min after fertilization. Among the treated groups, maximum hatching of 62% was obtained in cold shock at 2 °C for 15 min, whereas hatching percentage of control was 77.5%. After 30 days of rearing, the survival percentage of gynogens was very poor (2.3%). The mean length and weight of the gynogens were 48±0.2 mm and 2.82±0.2 g respectively. The normal diploids had a higher survival rate of 70.13% and the mean length and weight were 32±0.2 mm and 0.9±0.1g respectively.